INDEX DE NOMS D'AUTEURS/AUTHOR INDEX - Alley, Doreen; Amey, Gerald X.; Batty, David; Brunet, Lise; Bussy, Didier; Cakarnis, John; Campbell, H. C.; Carroll, John M.; Chaput, Gilles; Converse, W. R. M.; Desgagnes, Jean-Eudes; Djoric, Nicolas; et al. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF